AMBIENT LIGHT MONITORING SYSTEM USING INTERNET OF THINGS (IoT) - ABDUL MANAB, MUHAMMAD HARIZ (Universiti Teknologi PETRONAS, 2017)
Nowadays, the Internet of Things (IoT) technologies are ubiquitous and widely used by the users to solve their specific everyday life problems related with power usage consumption, environmental condition, automation and many more. An ambient light monitoring system is designed to measure the ambient light intensity or illuminance of particular indoor areas in UTP campus. This system is designed to take the light measurement autonomously and continuously without human involvement. The purpose of this project is to build a scalable IoT system to remotely monitor the ambient light level in real-time inside the indoor areas of the campus that supports multiple sensors with low power consumption. The system is a remote system which is using the concept of Internet of Things (IoT) where the integration of everyday devices and the Internet takes place to provide some specific information and do particular analytics. This project can be considered as a smart indoor environmental monitoring where the ambient light intensity of the indoor surrounding is measured autonomously or without human interference.